Politik Islam dan Demokrasi Kontemporer dalam Konteks Negara Bangsa Indonesia yang Plural Demokratis Modern Berkelanjutan (Pusat Riset dan Inovasi Nasional, 2026)
This article examines the relationship between Islamic politics and democracy in contemporary Indonesia. As the country with the largest Muslim population in the world, Indonesia presents a distinctive dynamic in the interaction between Islamic values and modern democratic systems. This study aims to analyze how Islamic political actors, including political parties and religious organizations, interact with and adapt to democratic practices in the post-Reform era. The research employs a qualitative method through a literature review of Indonesian academic journals published within the last five years. The findings indicate that Islamic politics in Indonesia is plural and dynamic, showing an adaptive tendency toward democratic principles. Islamic values such as deliberation (shura), justice, and equality are considered compatible with democratic ideals. However, Islamic politics also faces contemporary challenges, including the politicization of religion, identity politics, and social polarization. The article concludes that the relationship between Islamic politics and democracy in Indonesia is dynamic and largely adaptive within the framework of the Pancasila state.